Mechanical and processing properties of recycled PET and LDPE-HDPE composite materials for building components - Gonzalez Laria, Julian (2020)
Although several reports can be found in the literature about the recycling of plastic materials, only a few focus on recovering and molding them in a new process. Plastic material blends can be fabricated using several techniques, which allows the molding of a compound adaptable to each needed performance. This fact favors the recycling by allowing the use of mixed wastes without major processes, avoiding expensive treatments. This research work analyzes the mechanical properties of a material conformed by 100% recycled plastics: polyethylene terephthalate and low-/high-density polyethylene without previous separation or washing and drying pretreatments. Its macro and microscopic structure was studied and described, and formulations of different compound rates were analyzed. Mechanical resistance was around 60% of a material composed of virgin materials in compressive, flexural, and tensile strength tests. Its potential application to building components manufacture is analyzed.